Development of eco-efficient self-compacting concrete with waste marble powder using the response surface method - Alyamac, Kursat Esat; Ghafari, Ehsan; Ince, Ragip (Elsevier Sci Ltd, 2017)
Marble sludge is a significant environmental problem for all countries that have a marble stone industry. The problem primarily originates from the impossibility of storing marble sludge. Absorbing, eliminating and recycling waste marble sludge are of great importance in terms of the environmental health, environmental pollution and economic loss of countries. This research study aimed at developing an eco-efficient, eco-friendly and workable self-compacting concrete with the maximum amount of marble powder using the Response Surface Methodology. First, the relationships were determined among the water-to-cement and marble powder-to-cement ratios and the responses, such as slump flow, T-50, V-funnel and compressive strength. Next, a multi-objective optimization technique was used to achieve an eco-efficient self-compacting mixture design with the maximum possible amount of marble powder. As a result, an eco-efficient SCC was obtained with the water-to-cement-ratios less than 0.55 and the marble powder-to-cement-ratios of up to 0.6. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Self-compacting concrete; Response surface method; Optimization; Marble powder; Eco-efficient